The effect of ovarian reserve and receptor signalling on granulosa cell apoptosis during human follicle development - Regan, S.; Knight, P.; Yovich, John; Stanger, J.; Leung, Y.; Arfuso, Frank; Almahbobi, Ghanim; Dharmarajan, Arunasalam (Elsevier Ireland Ltd, 2017)
The poor oocyte quality in older women has previously been linked to the depletion of the ovarian reserve of primordial follicles and an increase in granulosal apoptosis. Granulosa cells were collected from 198 follicles and individually analysed by flow cytometry. In the young IVF patients, the level of apoptosis was inversely proportional to the expression of bone morphogenetic protein (BMPR1B) and follicle stimulating hormone (FSH) receptors. Conversely, in the older patients this relationship became dysregulated. In the older patients, at the time of preovulatory maturation, the reduced apoptosis reflects the poor mitogenic growth turnover rate of healthy follicles rather than the death rate in an atretic follicle. Restoring an optimum receptor density and down-regulation of receptors may improve oocyte quality and the pregnancy rate in older women.